2008
DOI: 10.1007/s11692-008-9028-5
|View full text |Cite
|
Sign up to set email alerts
|

The Yank of Dobzhansky’s Bequest

Abstract: Dobzhansky studied mechanisms of balancing selection using systems of inversions in Drosophila and he soon found that changes in inversion frequencies along generations in experimental populations conformed to the expectation for a simple model of heterosis. However, other more complex modes of selection, like rare male advantage, were later found to affect the maintenance of inversion polymorphisms. Here we show that a more realistic (and complex) model than heterosis-integrating all known fitness component e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Chromosome rearrangements have previously been argued to be adaptatively significant in Carex (Faulkner, 1972; Luceño & Castroviejo, 1991; Bell, 1982), as they have been for numerous other organisms (e.g. Alvarez‐Castro & Alvarez, 2005; Butlin, 2005; Alvarez‐Castro & Carlborg, 2008; Hoffmann & Rieseberg, 2008). The current study is the first to demonstrate that chromosome number itself – which may be a result of many independent and different rearrangements – may be in part a product of correlation with life‐history traits or (more weakly supported) adaptation to the environment.…”
Section: Discussionmentioning
confidence: 96%
“…Chromosome rearrangements have previously been argued to be adaptatively significant in Carex (Faulkner, 1972; Luceño & Castroviejo, 1991; Bell, 1982), as they have been for numerous other organisms (e.g. Alvarez‐Castro & Alvarez, 2005; Butlin, 2005; Alvarez‐Castro & Carlborg, 2008; Hoffmann & Rieseberg, 2008). The current study is the first to demonstrate that chromosome number itself – which may be a result of many independent and different rearrangements – may be in part a product of correlation with life‐history traits or (more weakly supported) adaptation to the environment.…”
Section: Discussionmentioning
confidence: 96%
“…As pointed out above, numerous studies found complex modes of selection to occur in the maintenance of Drosophila inversion polymorphisms reviewed in [19–21]. Furthermore, the stage-, sex-, and frequency-dependent fitness estimates obtained in competition experiments of Drosophila pseudoobscura have been successfully used to replicate the trajectories of frequencies of experimental populations along generations [25], which supports those multifaceted fitness estimates—instead of the minimal MCV with heterosis—as the selection mechanisms underlying the maintenance of inversion polymorphisms in experimental populations. Similarly, it cannot be argued that selection in heterogeneous environments is the only force maintaining the polymorphisms, since other balancing forces (different from heterosis) are known to act within niches.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has recently shown a more than reasonably good fit of predicted-to-observed trajectories, using from the last ones only their starting points [25, 26]. However, this positive result is not sufficient for completely understanding the balanced inversion polymorphisms of Drosophila's natural populations, with individuals migrating among niches with different selection pressures [27–30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation